2021
DOI: 10.1099/jgv.0.001513
|View full text |Cite
|
Sign up to set email alerts
|

Lysine 164 is critical for SARS-CoV-2 Nsp1 inhibition of host gene expression

Abstract: The emerging pathogen severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused social and economic disruption worldwide, infecting over 9.0 million people and killing over 469 000 by 24 June 2020. Unfortunately, no vaccine or antiviral drug that completely eliminates the transmissible disease coronavirus disease 2019 (COVID-19) has been developed to date. Given that coronavirus nonstructural protein 1 (nsp1) is a good target for attenuated vaccines, it is of great significance to explore the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Expression of SARS-CoV nsp1also inhibits cell proliferation and increases the number of cells in G0/G1 phase without affecting cell viability [64]. Likewise, SARS-CoV-2 nsp1 expression induces G0/G1 phase arrest [75]. Also, nsp1 of α-CoV, including TGEV, PRCV, SADS-CoV, PEDV, HCoV-229E, or HCoV-NL63, arrests the cell cycle at the G0/G1 phase in expressing cells [77].…”
Section: Cov Nsp1-induced Cell Cycle Arrestmentioning
confidence: 99%
“…Expression of SARS-CoV nsp1also inhibits cell proliferation and increases the number of cells in G0/G1 phase without affecting cell viability [64]. Likewise, SARS-CoV-2 nsp1 expression induces G0/G1 phase arrest [75]. Also, nsp1 of α-CoV, including TGEV, PRCV, SADS-CoV, PEDV, HCoV-229E, or HCoV-NL63, arrests the cell cycle at the G0/G1 phase in expressing cells [77].…”
Section: Cov Nsp1-induced Cell Cycle Arrestmentioning
confidence: 99%
“…On its hand, BRDT is required for expression of Ccna1 (Cyclin A1) during spermatogenesis [69,70]. Importantly, SARS-CoV-2 nsp1, which is involved in inhibition of host protein expression, has been shown to induce cell cycle arrest in G0/G1 phase [71].…”
Section: General Bet Functionsmentioning
confidence: 99%
“…Noteworthily, the recent study demonstrated that the nsp1 protein of SARS-CoV-2 could bind to 40S and 80S ribosomes and interfered with cap-dependent translation in host cells (56). And the key residue in nsp1 to inhibit host gene expression, a lysine, has been proven to be located at amino acid site 164 (K164) (57).…”
Section: Interfere With Host Biological Activitiesmentioning
confidence: 99%